(untitled) (International Journal of Scientific Trends, 2024)
This scientific article presents the results of laboratory and field experimental studies on the study of patterns of changes in the structural strengths of moistened loess soils under dynamic influences, depending on various external and internal factors. Recommendations have been developed for determining the design pressure based on buildings, taking into account changes in the strength characteristics of loess soils under seismic influences.